2016
DOI: 10.3991/ijet.v11i02.5094
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Scratch in Compulsory Secondary Education

Abstract: Abstract-The article analyzes the impact that the use of Scratch has in a group of students of Compulsory Secondary Education in the development of the teaching unit. For this we have studied the evolution of creative thought and analyzed the considerations made by the different actors involved, students and teachers. Qualitative and quantitative data are intended to complement the type of evidence and notes in research design followed. The tools used were the interview, field notes, diary of the researcher an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
1
9
0
2
Order By: Relevance
“…According to Ortiz-Colon and Romo (2016) and McGill (2012), learners' attitudes are favourably influenced by robotic applications. LEGO® MINDSTORMS® robotics education kit garnered learners' attention and boosted their enthusiasm for related reading (McGill 2012).…”
Section: Educational Roboticsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ortiz-Colon and Romo (2016) and McGill (2012), learners' attitudes are favourably influenced by robotic applications. LEGO® MINDSTORMS® robotics education kit garnered learners' attention and boosted their enthusiasm for related reading (McGill 2012).…”
Section: Educational Roboticsmentioning
confidence: 99%
“…LEGO® MINDSTORMS® robotics education kit garnered learners' attention and boosted their enthusiasm for related reading (McGill 2012). Furthermore, according to Ortiz-Colon and Romo (2016), LEGO®-based applications boost learner interest in academics. It was found that learners actively engaged in robot-related activities and that these activities effectively encouraged them.…”
Section: Educational Roboticsmentioning
confidence: 99%
“…The purpose of making this software is to ease high school and college students in learning programming and electronics. Moreover, S4A can improve high school students' motivation and performance according to references (Ortiz-Colón, 2016). Arduino programming can be easily applied to pictorial blocks with the help of S4A.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop these learning resources, teachers have made use of the technological resources at each point in time. Thus, immediately before the introduction of new technologies, physical means were usually employed, such as [38] books providing the grammar contents and the exercises to exercise vocabulary and grammatical structures, reading books in the language being studies, adapted to the various skill levels, bilingual printed dictionaries, tapes or discs with sound recordings used for aural comprehension, videos to work on audiovisual comprehension (verbal and nonverbal language), vocabulary flash cards, etc. These resources were effective (and in fact some of them are still used), but they had some limitations which will be discussed [40].…”
Section: Introductionmentioning
confidence: 99%
“…The success of this simple programming language is due to several factors [28], mainly the use of typical gaming elements to motivate and facilitate the learning of programming, the possibilities for innovation and creativity offered to create educational resources in the form of animated stories [12], the great capacity for configuration and adaptability (as own or created images, backgrounds, and sounds can be used), and the vast number of available resources to work with Scratch [37], given that the software as well as the programs created are free, and anyone can access the programs created by other people, copy them, reuse them, modify them, etc. Likewise, the project gives users a set of supporting learning materials, such as manuals, videos, FAQs, and support for teachers.…”
mentioning
confidence: 99%